Smart Mobile Application for Detecting Balinese Masks to Introduce Balinese Culture to World Tourism - Putu Gede Surya Cipta Nugraha; Putu Satria Udyana Putra; I Putu Agus Eka Darma Udayana; I Putu Dwi Guna Ambara Putra (SEAN Institute, 2023)
Indonesia, known for its remarkable cultural diversity, encompasses many ethnic groups, each preserving its distinct cultural heritage. Among Indonesia's cultural treasures is the ancient art of traditional mask-making, referred to as